2016
DOI: 10.4103/1658-354x.177325
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dexmedetomidine as an adjuvant to ropivacaine in pediatric caudal epidural block

Abstract: Context:Caudal analgesia is a reliable and an easy method to provide intraoperative and postoperative analgesia for infraumbilical surgeries in pediatric population but with the disadvantage of short duration of action after single injection. Many additives were used in combination with local anesthetics in the caudal block to prolong the postoperative analgesia.Aim:We compared the analgesic effects and side effects of dexmedetomidine added to ropivacaine in pediatric patients undergoing lower abdominal surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
3
10
0
1
Order By: Relevance
“…Kamal et al reported that addition of DEX to caudal ropivacaine significantly prolongs analgesia in children undergoing lower abdominal surgeries. [ 16 ] Goyal et al reported that DEX as adjuvant to bupivacaine increases duration of caudal analgesia and improves hemodynamic stability in children undergoing infraumbilical surgeries. [ 17 ] However, studies about DEX added to local anesthetics for caudal anesthesia in adult patients are fewer than that in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Kamal et al reported that addition of DEX to caudal ropivacaine significantly prolongs analgesia in children undergoing lower abdominal surgeries. [ 16 ] Goyal et al reported that DEX as adjuvant to bupivacaine increases duration of caudal analgesia and improves hemodynamic stability in children undergoing infraumbilical surgeries. [ 17 ] However, studies about DEX added to local anesthetics for caudal anesthesia in adult patients are fewer than that in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 3 4 ] Dexmedetomidine a novel selective α-2 agonist with a favorable pharmacokinetic profile and versatility with slight concern of bradycardia, has shown promise as an adjuvant in neuraxial use as shown by many recent trials. [ 5 6 7 8 9 10 11 ] Dexamethasone with its analgesic, anti-inflammatory, and antiemetic properties has been safely used perineurally with good outcome in prolonging the analgesia as agreed with a number of studies. [ 9 12 13 14 15 ] Magnesium has reemerged as antinociceptive by regulating calcium influx into the cells.…”
Section: Introductionmentioning
confidence: 77%
“…used dexmedetomidine caudally with ropivacaine in children aged 2–10 years to study hemodynamic variables, end-tidal sevoflurane, and emergence time, postoperative analgesia, requirement of additional analgesic, sedation, and side effects for the first 24 h and concluded that dexmedetomidine group prolonged postoperative analgesia (750 vs. 390 min), without clinically significant side effects, sedation, or hemodynamic disturbances. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We monitored FLACC scores till requirement of rescue analgesic and found that the duration of analgesia was 10 h in the D2 group and 11 h in the D3 group. Kamal et al ( 20 ) studied the effect of 1 mL kg −1 of 0.25% ropivacaine with 2 μg kg −1 of dexmedetomidine given in caudal epidural space and found that the duration of analgesia is 750 min. Al-Zaben et al ( 21 ) found that 1 μg kg −1 of IV dexmedetomidine prolongs the effect of caudal analgesia up to 9 h. Our results show that 2 μg kg −1 of nebulised dexmedetomidine gives analgesia up to 10 h, and that 3 μg kg −1 prolongs the duration of analgesia up to 11 h. Olutoye et al ( 22 ) found that the duration of analgesia is significantly more with 1 μg kg −1 of IV dexmedetomidine than with 0.75 μg kg −1 of IV dexmedetomidine in paediatric patients undergoing tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%